Prime Time for Prime Funds: Floating NAV, Intraday Redemptions, and Liquidity Risk during Crises - Casavecchia, Lorenzo; Ge, Chanyuan; Wei Li, C; Tiwari, Ashish (The Review of Asset Pricing Studies, 2026)
This paper provides the first systematic evidence on a recent industry innovation: money market funds offering multiple intraday NAV strikes and redemption windows. Emerging after the 2016 floating-NAV reforms, these multistrike funds hold safer, more liquid assets than traditional single-strike funds offering end-of-day redemptions, yet face substantially larger outflows during periods of market stress. Our findings point to a structural concentration of liquidity-sensitive investors in multistrike funds, revealing how fund microstructure influences run dynamics among sophisticated institutions. Despite evolving liquidity requirements, the core behavioral and structural differences we identify remain highly relevant for evaluating ongoing and future regulatory reforms